Segregation and Gender Gaps in the United Kingdom's Great Recession and Recovery. Issue 4 (2nd October 2018) - Razzu, Giovanni; Singleton, Carl
ABSTRACT: This article assesses the role of segregation in explaining gender employment gaps through the United Kingdom's Great Recession and its subsequent period of recovery and fiscal austerity. The analysis reaffirms that gender employment gaps in the UK respond to the business cycle, and it evaluates to what extent these short-term changes in the employment gap can be explained by the industry sectors and occupations where women and men work. A counterfactual analysis accounts for the specific role of combined gender segregation across industry sectors and occupations that existed at the onset of the Great Recession. The results contradict the existing narrative that men's employment was more harshly affected than women's employment; segregation accounts for over two and a half times the actual fall in the gender gap between 2007 and 2011.